Cultural heritage as a field for EU’s action in external relations: the evolution of strategy and the Ukrainian check [version 1; peer review: 2 approved] - Dorota Jurkiewicz-Eckert (Stosunki Międzynarodowe)
The European Union’s systemic engagement in the field of cultural heritage in the external relations is a relatively new and still emerging area. This is a complex action field that requires the Union to find systemic solutions that will enable it to act effectively and make full use of cultural heritage as an instrument of its foreign policy. The process of conceptualising and adopting political decisions in order to introduce the protection, preservation and promotion of cultural heritage as a field of EU action in external relations lasted from 2016 to 2022. Influenced by internal and external factors, the concept on EU Approach to Cultural Heritage in External Action evolved. A few months before the outbreak of full-scale war in Ukraine in 2022, the Council of the European Union adopted Conclusions on EU Approach to Cultural Heritage in Conflicts and Crises. The war in Ukraine and Russia's destruction and threat to Ukrainian tangible and intangible cultural heritage has become a significant test of the EU's capabilities in this field. The text is divided into two parts. The first is an analysis of the process of integrating cultural heritage into the EU's strategy in external relations, while the second attempts to answer the question of how the EU has activated the mechanisms and instruments adopted to protect Ukraine's endangered cultural heritage in the face of Russia's systemic destructive measures.